The radiosensitizing effects of Nelfinavir on pancreatic cancer with and without pancreatic stellate cells. Issue 2 (May 2016) - Al-Assar, Osama; Bittner, Martin-Immanuel; Lunardi, Serena; Stratford, Michael R.; McKenna, W. Gillies; Brunner, Thomas B.
Abstract: Aims: We have previously shown in a phase I trial that nelfinavir (NFV) is safe with chemoradiation in PDAC with good signs for efficacy. Reverse translationally, we aimed to test the influence of PSCs on nelfinavir mediated radiosensitization to PDAC preclinically, because PDAC is very rich in desmoplasia and PSCs are known to mediate radioresistance. Methods: In a direct co-culture model of several PDAC cell lines with PSC we performed clonogenic assays +/− nelfinavir. This was repeated exposing cells to hypoxic conditions. In xenograft PDAC tumors we tested radiation +/− nelfinavir +/− PSC. Results: NFV sensitized both, PDAC only and PDAC cocultured with PSC (PDAC: Panc-1, MiaPaCa-2, PSN-1). In Panc-1 and PSN-1 this effect was larger +PSC compared to −PSC. Human pancreatic stellate cells (hPSC) were also sensitized by NFV which reduced p-FAK levels in hPSC, an effect that we previously found to sensitize specifically PDAC/PSC coculture. Contrarily, LY294002 reduced p-Akt in PSC (hPSC and LTC-14) but had no impact on PSC radiation survival. In vitro, nelfinavir sensitized Panc-1 and PSN-1 under normoxic and hypoxic conditions. In PSN-1 xenografts, +PSC led to faster tumor regrowth after radiation vs −PSC. The regrowth delay effect of nelfinavir after radiation was dramatically larger +PSC vs −PSC (time to reach 250 mm 3 183% vs 22%). Conclusion: NFV mediated radiosensitization in PDAC with stroma is partly mediated by p-FAK inhibition (Chen et al., 2013). In vitro, NFV sensitizes both normoxic and hypoxic PDAC +/− PSC to a roughly similar extent. The dramatic increased effect of xenograft regrowth inhibition by nelfinavir in tumors with PSC is attributed to vascular normalization (Brunner et al., 2014) rather than direct modification of hypoxia as shown by the tumor regrowth after gemcitabine with NFV.